Conservation implications of invasive animal species (Zoological Records and Reviews, 2025)
Invasive alien animal species (IAAS) are the second leading cause of global biodiversity loss after habitat destruction, yettheir conservation implications vary enormously with invasive species identity, invaded ecosystem type, and thevulnerability of native assemblages. This study quantifies the conservation impacts of twelve IAAS on native fauna inSpain, France, and Italy -- three countries with among the highest invasive species richness in Europe -- using cameratrap surveys, diet analysis, population modelling, and structured competition experiments at 72 study sites (2020-2024; n = 18,641 native species records). Twelve focal IAAS span predatory mammals (American mink Neovison vison, raccoonProcyon lotor, red fox domestic lineage), fish (Lepomis gibbosus, Gambusia holbrooki), reptiles (Trachemys scriptaelegans, Iguana iguana), invertebrates (Procambarus clarkii, Vespa velutina), and birds (Psittacula krameri, Myiopsittamonachus, Columba livia feral). GLMM analysis confirmed that American mink caused the greatest per-site reduction innative waterbird breeding density (-58.4 +- 7.8%; z = -7.48, p < 0.001) and amphibian community richness (-42.4 +-6.8%) of any focal IAAS. Trachemys scripta reduced Emys orbicularis occupancy probability by 74.8% at invaded sites.Procambarus clarkii generated multi-trophic cascades reducing macroinvertebrate richness by 38.4% and waterbirdforaging success by 28.4%. Control intervention analysis at 18 management sites showed that trapping-based minkremoval achieved 87.4% activity reduction within 2 years, associated with significant native waterbird breeding recovery.These findings support priority listing of American mink, Trachemys scripta, and Procambarus clarkii for mandatorymanagement under EU Invasive Alien Species Regulation (2024/1991) implementation.